Characteristics of Liquid Organic Fertilizer from Vegetable Waste Fermented with Various EM4 Concentrations and Its Effects on the Growth of Green Spinach (Amaranthus hybridus L.) - Anggi Indah Yuliana; Mohamad Nasirudin; Ainin Mukarromah (AGARICUS: Advances Agriculture Science & Farming, 2026)
Green spinach (Amaranthus hybridus L.) is a high-value leafy vegetable commodity that requires optimal nutrient availability from the early stages of growth. Utilizing vegetable waste as liquid organic fertilizer (LOF) with EM4 and molasses bioactivators serves as an alternative solution for sustainable cultivation.  This study aimed to analyze the physical characteristics of vegetable waste LOF under various EM4 and molasses concentrations, and to evaluate the effect of its application dosage on the vegetative growth and physiological components of green spinach. The research was conducted from February to June 2026 using a Factorial Randomized Block Design (RBD) with two factors and three replications. The first factor was the type of LOF based on EM4 and molasses concentrations (P1: 0 ml, P2: 20 ml, P3: 40 ml, P4: 60 ml). The second factor was the LOF application dosage (D1: 15 ml L⁻¹ dan D2: 30 ml L⁻¹). The results indicated that increasing EM4 and molasses concentrations altered the LOF color to dark brown and intensified the fermented tape-like aroma, while maintaining a stable temperature (33,29–34,08°C). Variations in the LOF type exerted no significant effect on any growth parameters of the spinach. Conversely, the application dosage factor had a significant independent effect during the early growth phase (21 days after planting / DAP). The 15 ml L⁻¹ (D1) produced a significantly higher number of leaves, leaf area (11,32 cm²), fresh weight (0.45 g), dry weight (0.035 g), Relative Growth Rate/RGR (0,74 g g⁻¹ day⁻¹), and Net Assimilation Rate/NAR (0,0075 g cm⁻² day⁻¹) compared to the 30 ml L⁻¹ dosage (D2).